Surgical site Infection after gastrointestinal and hepatobiliary surgeries- A retrospective evaluation from a single center of western India - Vasavada, Bhavin; Patel, Hardik (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Aim of our study to evaluate various factors responsible for surgical site infection after gastrointestinal and hepatobiliary surgeries. Methods: Patients who underwent gastrointestinal and hepatobiliary surgery in our department were evaluated retrospectively. Various factors associated with surgical site infection were evaluated using univariate and multivariate analysis. Surgical site infection was defined as any culture positive discharge from the wound within 30 days of surgery. Results: We evaluated a total of 331 patients operated between April 2018 and March 2020. 14 patients were lost to follow up after discharge and before completing post operative day 30. Eighteen patients expired before 30 days without developing SSI and were excluded from the study as per exclusion criteria. 299 patients were included in the study. Twenty patients developed surgical site infection. It showed SSI rate in our study population was 6.68%. On univariate analysis prolonged hospital stay, more blood product used, higher CDC grade of surgery, higher ASA grade, more operative time, open surgeries, colorectal and HPB surgeries were associated with surgical site infections. On multivariate analysis only prolonged hospital stay independently predicted SSI. (p=0.014, Odds ratio 1.223, 95% confidence interval 1.042-1.435.). Conclusion: Prolonged hospital stay independently predicts surgical site infections after gastrointestinal and hepatobiliary surgery.